PROPOSED STRATEGY FOR PT RESIK NYAMAN SEJAHTERA PENETRATING CLEANING AND SECURITY SERVICE MARKET USING AHP METHOD - Raharja, Indra; Hugo, Prasetyo (Dinasti International Journal of Digital Business Management, 2021)
The background of research is PT Resik Nyaman Sejahtera experiences several problems in the company: The company does not have clear targets, no marketing ,human resources and operations programs, unstable sales, high employee turnover. Therefore, the purpose of this study is to determine the factors that affect cleaning and security service business in Jakarta. To find out the company's strategy can still compete with current conditions. To formulate a business strategy company’s keeps the cleaning and security service business stay competitive in Jakarta. This research is a qualitative descriptive study by conducting interviews with owners, mapping the company's external and internal factors, weighting using Analytic Hierarchy Process, mapping company strategy with the Grand Matrix Strategy and Michael Porter's Five Generic Strategy. The results of this study provide the best strategies in marketing, operations, human resources, and corporate financial information systems in the next five years to achieve a competitive advantage.